Effectiveness of Pharmacist Intervention to Reduce Medication Errors and Health-Care Resources Utilization After Transitions of Care: A Meta-analysis of Randomized Controlled Trials. Issue 5 (30th August 2021) - De Oliveira, Gildasio S.; Castro-Alves, Lucas J.; Kendall, Mark C.; McCarthy, Robert
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: Medication errors are common during transitions of care. The main objective of the current investigation was to examine the effectiveness of pharmacist-based transition of care interventions on the reduction of medication errors after hospital discharge. Methods: A systematic search was conducted to detect published reports of randomized trials using the National Library of Medicine's PubMed database, the Cochrane Database of Systematic Reviews, and Google Scholar inclusive to July 1, 2015. Search terms included pharmacist, medication, errors, readmission, transition, and discharge . A priori main outcomes included medication errors and health-care resources utilization (hospital readmission and/or emergency room visits). Quantitative analysis was performed using a random effect method. Results: Thirteen randomized trials examining 3503 patients were included in the final analysis. The aggregate effect of the 10 studies evaluating the effect of pharmacists intervention on the incidence of medication errors during transitions of care favored pharmacist over control with an odds ratio (95% confidence interval [CI]) of 0.44 (0.31–0.63). The overall effect of 4 studies evaluating the effect of a pharmacist intervention on the incidence of emergency room visits compared with control favored the pharmacist intervention, odds ratio (95% CI) of 0.42 (0.22–0.78), number needed to treat (95% CI) of 6.2 (3.4–31.4). Conclusions: Pharmacist transition of care intervention is an effective strategy to reduce medication errors after hospital discharge. In addition, a pharmacist intervention also reduces subsequent emergency room visits. Hospitals should consider implementing this intervention to improve patient safety and quality during transitions of care.